PEMANFAATAN CAMPURAN ZEOLIT DAN FLY ASH BATUBARAYANG TELAH DIAKTIVASI FISIK TERHADAP AKSELERASI MESIN SEPEDA MOTOR 4-LANGKAH - Herry Wardono; Ahmad Yudi Eka Risano; Adi Ernadi (Universitas Muhammadiyah Metro, 2018)
Energy consumption in Indonesia is quite high, almost 96% is supplied from fossil fuel ( crude oil 48%, gases 18%, and coal 30%). From the total of energy consumption, it can be seen that almost 50% is gasoline. Thus, it is necessary to attain a certain aim in saving fossil fuel consumption. One of the ways is the utilization of zeolite and coal fly ash mixture as engine air filter. The mixture of zeolite and coal fly ash have a specific ability to trap nitrogen gases and water vapor in air, so that only oxygen enters the combustion chamber. Thus, the combustion process reaches the optimal condition and engine performance works better. Before applying, zeolite and fly ash were mixed with the comparisons of zeolite 0% : fly ash 100%, zeolite 25% : fly ash 75%, zeolite 50% : fly ash 50%, zeolite 75% : fly ash 25%, and zeolite 100% : fly ash 0%. The mixture of zeolite and fly ash was made in the form of pellet and activated physically within the temperature of 100 ºC (naturally), 150 ºC, 175 ºC, 200 ºC, and 225 ºC. Wheres various mass filter used were 50% (13,75 grams), 75% (20,62 grams) and 100% (27,50 grams). The pellets were arranged resemble a filter and place on the case of engine air filter. The purpose of this testing is to find out the effect of temperature activation and the filter mass variations as well as the composition of zeolite and fly ash mixture toward the performance of four step gasoline engine in acceleration testing. The best acceleration achieved is 12,61% (2,41 seconds faster ) taken from the test using filter of Z50:F50 mixture, with mass variation of 100% within temperature of 225 °C.Keywords: Filter of zeolite and coal fly ash,air adsorbent, engine acceleration.